Can Profit-shifting be Resolved by Penalization? - Tomáš Buus; Jaroslav Brada (European Financial and Accounting Journal, 2010)
We examine contemporary practice of transfer pricing rules enforcement in this paper. We have used neoclassical microeconomic framework with transfer price estimated via comparable uncontrolled price method. We have found that if vertically integrated multinational enterprise (MNE) has possibility to evade tax through transfer pricing, then it produces higher quantity of final product, than it would if no possibility of tax evasion existed. Secondly we have found that although nowadays' transfer pricing rules require use of enforcement instruments (penalty), there is no penalty high enough to extinguish tax evasive transfer pricing totally, and if market for the product produced in country with high tax rate is perfectly competitive or there is monopolistic competition, no optimal penalty can be found. That changes at oligopolistic, monopolistic or duopolistic market of that product – there we could find optimal penalty.
Keywords: D21; D29; G39; 650; Tax evasion; Transfer prices; Multinational enterprises